Implementing the Policy to Serve Citizens (BMW) in Tulang Bawang Regency: Public Service Innovation Study - Winarti; Murtir Jeddawi; Sampara Lukman; Agus Fatoni (GoAcademica Research & Publishing, 2021)
This study examines the implementation of the